THE BRONZE-EARLY IRON AGE OF NAKHCHIVAN CORRECTED - Toğrul Halilov (International Journal of Eurasia Social Sciences, 2012)
The article studies the corrected in IV-I millenniums B.C. It was defined that pottery wasone of the ancient craftsmanship areas in Nakhichivan. At that time Nakhichivan, as well as the other regions of Azerbaijan, was an important centre of craftsmanship. The pottery products differed from one another in their size, shape, ornaments on them, the material the were made of and the technology. The pottery products made by Nakhichivan potters were divided into two groups-welfare and kitchen ceramics. Their similar monuments in the South Caucasus and the Middle East in the same period, the archaeological materials found in the Urmia basin and Eastern Anatolia.debates on abortion information on abortion nyc abortion clinics